Learning to See New Things: Using Criteria to Support Pre-service Teachers' Discernment in the Context of Teachers' Relational Work - Holmstedt, Pernilla; Jönsson, Anders; Aspelin, Jonas (Frontiers in Education, 2018)
The purpose of this study was to investigate how pre-service teachers' understanding of relational competence can be supported through the use of digital video and explicit criteria. The study is a mixed method intervention study, where pre-service teachers analyzed the teacher-student relationship as depicted in a short video sequence with the support of explicit criteria. These analyses were analyzed with content analysis according to the criteria and a thematic comparison of pre-service teachers' analyses before and after the access to explicit criteria. Findings suggest that the use of explicit criteria supported pre-service teachers' discernment of significant dimensions of teacher-student relationships, so that they were able to discern and discuss aspects of the teacher-student relationship with a specific focus on teacher-student interaction and with greater detail and nuance. The study also provides some tentative evidence that modeling the use of criteria may support pre-service teachers' use of the criteria.